A STRUCTURAL EQUATION MODEL OF THE DETERMINANTS AFFECTING STUDENTS’ BEHAVIORAL INTENTION AND SATISFACTION TOWARDS BLENDED LEARNING OF ENGLISH AS A FOREIGN LANGUAGE AT A BANGKOK PUBLIC UNIVERSITY - Nuamsamrarn, Saowalux; Achwarin, Naree (Journal of Education and Innovation, 2023)
This research intends to investigate the determinants based on the integration of Theory of Planned Behavior (TPB) and Technology Acceptance Model (TAM). By integrating TPB and TAM, the researcher developed a conceptual model of the relationships between factors that affected behavioral intention and satisfaction towards using Google Classroom as a blended learning system in an EFL course. The research was conducted in a Bangkok Public University, with 354 first-year undergraduate EFL students who enrolled in the English foundation course via an online questionnaire. The Structural Equation Model (SEM) was employed for hypotheses testing. The result revealed 7 interesting determinants which had significant positive effects with Behavioral Intention (BI) and Satisfaction (S) to use Google Classroom as a blended learning system in an EFL course; 1) Perceived Ease of Use (PEOU), 2) Perceived Behavior Control (PBC), 3) Subjective Norm (SN), 4) Computer Self-Efficacy (CSE), 4) Social Presence (SP), 5) Collaborative Learning (CL), 6) Facilitating Conditions (FC), and 7) Task-Technology Fit (TTF). In addition, the research found that all 8 determinants had a significant positive direct effect on behavioral intention. The strongest direct effect is TTF ( = 0.748, p-value = 0.000). Moreover, PEOU, SP, CL, FC, and TTF had a positive direct effect on satisfaction. The strongest direct effect is TTF ( = 0.771, p-value = 0.000). Furthermore, CSE was the only determinant which a had significant indirect effect on both behavioral intention ( = 0.275) and satisfaction ( = 0.289). In SEM, the goodness of fit indices met seven specified criteria of model fit acceptance ( 2/df = 1.647, RMSEA = 0.043, SRMR = 0.033, NNFI = 0.938, TLI = 0.961, CFI = 0.974, and GFI = 0.929). The result indicated a strong fit between the structural model and the data.